Role of P2Y1 purinoceptor in ADP-induced platelet activation - Savi, P; Beauverger, P; Labouret, C; Delfaud, M; Salel, V; Kaghad, M; Herbert, J.M (FEBS letters, 1998)
ADP acts as an agonist of platelet aggregation via specific receptors which are still to be characterised. Amplification by PCR of a human platelet cDNA library confirmed the presence of mRNA of the P2Y1 receptor in platelets. In order to determine if these P2Y1 receptors were involved in ADP-induced platelet activation, we determined the effects of A3P5PS, an antagonist of the P2Y1 receptor, on the binding of [ 33P]2-MeS-ADP, a potent analogue of ADP. We found that A3P5PS displaced about 27% of [ 33P]2-MeS-ADP binding, a receptor population which has been shown to be resistant to treatment with clopidogrel, a selective anti-ADP agent. A3P5PS specifically inhibited 2-MeS-ADP-induced shape change and calcium increase but did not affect adenylyl cyclase down-regulation. 2-MeS-ADP-induced platelet aggregation was also inhibited by A3P5PS but was restored when platelets were further activated by serotonin, a non-aggregating compound, therefore suggesting that P2Y1-mediated stimulation is an absolute prerequisite for ADP to induce platelet aggregation and a key event for platelet activation and aggregation to occur. These results therefore show that ADP-induced aggregation cannot be attributed to activation of P2Y1 alone, but must be attributed to the simultaneous activation of the high affinity receptor (P2Y1) and a low affinity receptor of ADP (still to be discovered), each of them essential, but neither able to trigger aggregation alone.